Exploring antimicrobial properties and oral health benefits of salix subserrata willd: unveiling the potential beyond its use as traditional chewing stick - Fekade Beshah Tessema; Tilahun Belayneh Asfaw; Mesfin Getachew Tadesse; Rakesh Kumar Bachheti; Yilma Hunde Gonfa; Dawit Sitotaw Addisie; Terefe Gebremariam Aregahegn; Tigist Getachew Tadesse; Megersa Aboneh (BMC Complementary Medicine and Therapies)
Abstract Background Salix subserrata is one of the traditional chewing sticks used commonly in Ethiopia. It is also used traditionally against rabies and other infections. There has been no comprehensive research on the biological activity of this plant to demonstrate its role in maintaining oral health. Given the compounds previously isolated from this species, this study aims to predict which extracts among the four solvents are responsible for promoting oral health. Method The phytochemical content and antioxidant activity of the leaves, stem, and stem bark extracted with four different solvents were evaluated using standard methods. The EC50 of the extracts was tested with the DPPH assay, and the silicon content of the stem was determined by a gravimetric method. The antibacterial activity was tested using an agar well diffusion method at different test concentrations of (mg/ml) crude extracts and MIC/MBC were determined using the microdilution method. Physicochemical and ADME properties were determined using the SwissADME online server. PASS online was used to predict biological activities related to the oral health of the compounds previously isolated from the plant. Results The antioxidant activity, in terms of EC50, of the leaves of S. subserrata was comparable to that of the standard reference, ascorbic acid. The silicon content in the stem extract of the plant was found to be 0.24%. The leaves of S. subserrata exhibited higher levels of total phenolic and flavonoid contents compared to other parts of the plant. Hexane, chloroform, and ethyl acetate extracts of S. subserrata were found to be active against the Gram-positive bacteria (Listeria monocytogenes and Enterococcus faecalis) which are known to be responsible for foodborne infections. Among the previously reported compounds from S. subserrata, catechin, quercetin, saligenin, catechol, gallocatechin, salicin, and triandrin were found to be predicted for the strong antioxidant, anti-infection, and anti-mucositis activities. Conclusion All phytochemical analysis and antimicrobial activity results underscore the significance of plants traditionally used as chewing sticks. The roles of previously isolated compounds in maintaining oral health were also predicted, though toxicity tests and comprehensive profiling of the extracts necessitate further investigation.